mRNA Vaccines in Glioma: Antigen Selection, Immune Profiling, Comprehensive Strategies and Challenges - Yang, Fan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Glioma is one of the most invasive primary brain tumors, and the exploration of its treatment strategies has always been a focus in the field of neurooncology. In recent years, mRNA vaccine technology has shown great potential in the COVID-19 epidemic, and its application in the treatment of glioma has also attracted increasing attention. This article reviews the research progress of mRNA vaccines in the treatment of glioma, including the advantages and challenges of mRNA vaccines, the comparison of different RNA therapy methods, as well as the screening of tumor specific antigens, differentiation of immune subtypes, and development of comprehensive treatment strategies. Although mRNA vaccines have shown promising prospects in the treatment of gliomas, their clinical translation still faces challenges such as safety, production scale, and cost-effectiveness. The author believes that a deep understanding of the molecular mechanisms of glioma and the heterogeneity of the immune microenvironment is crucial for developing effective mRNA vaccines. Future research needs to make breakthroughs in improving the stability of mRNA vaccines, optimizing immunogenicity, developing personalized vaccines, and comprehensive treatment strategies.